Fiber-reinforced resin composite material and method for producing the same

In-situ polymerizable thermoplastic resins effectively impregnate natural fibers, enhancing mechanical strength and reducing water absorption in fiber-reinforced resin composites by minimizing porosity, addressing the limitations of existing materials.

JP2025005481APending Publication Date: 2025-01-17NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023105634
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Natural fibers have a hollow structure that existing thermoplastic resins like polypropylene and polyamide 66 cannot impregnate, leading to low mechanical strength and high water absorption in fiber-reinforced resin composites.

Method used

A fiber-reinforced resin composite material using an in-situ polymerizable thermoplastic resin, such as an in-situ polymerizable phenoxy resin, is impregnated into natural fibers to fill hollow portions, reducing porosity to 20% or less, thereby enhancing mechanical strength and reducing water absorption.

Benefits of technology

The composite material achieves improved mechanical strength and reduced water absorption by ensuring thorough impregnation of the natural fibers with the thermoplastic resin, maintaining structural integrity and moisture resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005481000001_ABST
    Figure 2025005481000001_ABST
Patent Text Reader

Abstract

To provide a fiber-reinforced resin composite material with enhanced mechanical strength and reduced water absorbency.SOLUTION: A fiber-reinforced resin composite material contains a natural fiber substrate and a matrix resin. The matrix resin is an in-situ polymerizable thermoplastic resin. The fiber-reinforced resin composite material has a voidage of 20% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced resin composite material containing a natural fiber base material and a matrix resin. [Background technology]

[0002] Toward the realization of carbon neutrality, fiber-reinforced resin composite materials using natural fibers as reinforcing fibers are being developed as materials with low CO2 emissions. Thermosetting resins and thermoplastic resins can be used as matrix resins in these fiber-reinforced resin composite materials, but thermoplastic resins are preferable in terms of recyclability and application to mass production.

[0003] As fiber-reinforced resin composite materials containing natural fibers and thermoplastic resins, Patent Document 1 discloses a molded body in which a spun yarn of natural fibers and polypropylene are integrally molded, Patent Document 2 discloses a spun yarn containing natural plant fibers and thermoplastic synthetic fibers such as polypropylene, and Patent Document 3 discloses a molded body containing natural fibers coated with a low-melting-point thermoplastic resin such as polypropylene and a high-melting-point thermoplastic resin such as polyamide 66. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-138361 A [Patent Document 2] International Publication No. 2011 / 062007 [Patent Document 3] JP 2005-68371 A Summary of the Invention [Problem to be solved by the invention]

[0005] Generally, natural fibers have a hollow structure. Polymers such as polypropylene and polyamide 66 used as thermoplastic resins in Patent Documents 1 to 3 cannot impregnate the hollow parts of natural fibers, and cannot impregnate the center of natural fiber substrates. Fiber-reinforced resin composite materials containing such natural fiber substrates have low mechanical strength and high water absorption, and therefore may not have sufficient mechanical strength both when absorbing water and when not absorbing water.

[0006] Therefore, an object of the present invention is to provide a fiber-reinforced resin composite material having improved mechanical strength and reduced water absorption. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides (1) a fiber-reinforced resin composite material containing a natural fiber base material and a matrix resin. The matrix resin is an in-situ polymerized thermoplastic resin. The porosity of the fiber-reinforced resin composite material is 20% or less.

[0008] (2) The fiber-reinforced resin composite material according to (1), wherein the natural fiber base material is any one of a unidirectional material, a woven fabric, and a knitted fabric made of spun yarn of plant fibers.

[0009] (3) A method for producing a fiber-reinforced resin composite material according to (1) or (2), comprising an impregnation step and a composite material production step. In the impregnation step, a precursor composition containing a monomer or oligomer, which is a raw material of an in-situ polymerization type thermoplastic resin, and a curing catalyst is impregnated into a natural fiber substrate. In the composite material production step, the monomer or oligomer impregnated into the natural fiber substrate by the impregnation step is polymerized to produce a fiber-reinforced resin composite material containing an in-situ polymerization type thermoplastic resin having a weight average molecular weight of 45,000 or more.

[0010] (4) A method for producing a fiber-reinforced resin composite material according to (1) or (2), comprising an impregnation step, a prepreg production step, and a composite material production step. In the impregnation step, a precursor composition containing a monomer or oligomer, which is a raw material of an in-situ polymerization type thermoplastic resin, and a curing catalyst is impregnated into a natural fiber substrate. In the prepreg production step, the monomer or oligomer impregnated into the natural fiber substrate by the impregnation step is polymerized to produce a prepreg in which a polymer having a weight average molecular weight of 1000 to 30000 is contained in the natural fiber substrate. In the composite material production step, the polymer contained in the prepreg is further polymerized to produce a fiber-reinforced resin composite material containing an in-situ polymerization type thermoplastic resin having a weight average molecular weight of 45000 or more. Effect of the Invention

[0011] In the fiber-reinforced resin composite material according to the present invention, the thermoplastic resin sufficiently penetrates into the hollow portions of the natural fibers contained therein, and the thermoplastic resin sufficiently penetrates into the center of the natural fiber substrate, thereby providing a fiber-reinforced resin composite material with improved mechanical strength and reduced water absorption. [Brief description of the drawings]

[0012] [Figure 1] 1 is a flowchart showing a method for producing a fiber reinforced resin composite material according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] (Structure of fiber-reinforced resin composite materials) The fiber-reinforced resin composite material according to the present invention contains a natural fiber base material and a matrix resin.

[0014] The natural fibers used in the present invention may include plant fibers such as jute, linen, ramie, hemp, cotton, kapok, kenaf, palm, coconut fiber, birch, rice straw, wheat straw, pineapple fiber, and bamboo fiber, as well as animal fibers such as silk and wool.

[0015] The form of the natural fiber substrate used in the present invention is preferably any one of unidirectional materials, woven fabrics, and knitted fabrics made of spun vegetable fiber yarns, but is not limited thereto. In order to improve the design, dyed fabrics and discarded clothing such as denim can also be used as the natural fiber substrate.

[0016] The basis weight of the natural fiber used in the present invention is not particularly limited, but is, for example, 100 g / m 2 More preferably, it is 300 g / m 2 That's all.

[0017] The matrix resin used in the present invention is an in-situ polymerization type thermoplastic resin. This "in-situ polymerization type thermoplastic resin" refers to a reactive precursor composition that is initially in the form of a monomer or oligomer, and can be rapidly polymerized in situ by heat or the like to be converted into a high molecular weight thermoplastic resin. As described in the "Problems to be Solved by the Invention" section, natural fibers generally have a hollow structure, and therefore the amount of voids in the fibers themselves is greater than that of synthetic fibers, carbon fibers, glass fibers, and the like. Thermoplastic fiber-reinforced plastics are generally produced by impregnating a fiber substrate with molten thermoplastic resin, but polymers (e.g., polypropylene and polyamide 66) that have been used as thermoplastic resins in the past are already in a fully polymerized state as polymers, and have very large molecular weights and high melt viscosities. Therefore, when such polymers are used as thermoplastic resins, they are not able to impregnate the hollow parts of the natural fibers when impregnating the natural fibers, and they are also not able to fully impregnate the spaces between the fibers of the fiber substrate, and in particular, they are not able to impregnate the center of the fiber substrate. In this way, when the hollow portions of the natural fibers and the center portion of the fiber substrate are not impregnated with the thermoplastic resin, (a) the mechanical strength of the fiber substrate itself is insufficient, and therefore the mechanical strength of the fiber reinforced resin composite material may be insufficient, and (b) if the hollow portions of the natural fiber substrate are not impregnated with the thermoplastic resin, water is likely to penetrate into the hollow portions, and therefore the water absorption of the fiber reinforced resin composite material may increase, and the mechanical strength of the fiber reinforced resin composite material when it absorbs water may decrease.

[0018] In contrast, in-situ polymerized thermoplastic resins have a sufficiently small molecular weight of monomers or oligomers and a low melt viscosity when impregnated into natural fibers, so they can penetrate into the hollow portions of the natural fibers through the walls and cross sections. In addition, the monomers and oligomers of the in situ polymerization type thermoplastic resin have reactive functional groups and are highly compatible with natural fibers having many surface hydroxyl groups. Furthermore, as described above, the monomers and oligomers have sufficiently small molecular weights and low melt viscosities. Therefore, the monomers or oligomers of the in situ polymerization type thermoplastic resin can be sufficiently impregnated into the center of the fiber substrate. Then, the monomer or oligomer is polymerized in situ to form a high molecular weight in situ polymerized thermoplastic resin, which is maintained in a state of impregnating the hollow portions of the natural fibers and the center of the fiber substrate. This sufficiently reduces the voids in the natural fibers and the natural fiber substrate, (A) improving the mechanical strength of the natural fiber substrate itself and imparting sufficient mechanical strength to the fiber reinforced resin composite material, and (B) preventing water from penetrating the natural fiber substrate and reducing the water absorption of the fiber reinforced resin composite material, thereby improving the mechanical strength of the fiber reinforced resin composite material when absorbing water.

[0019] Thus, in the present invention, the porosity of the fiber reinforced resin composite material can be reduced by impregnating the natural fiber substrate with an in-situ polymerized thermoplastic resin to reduce the voids. In order to achieve the effects (A) and (B) above, the porosity of the fiber reinforced resin composite material of the present invention is 20% or less. Preferably, the porosity of the fiber reinforced resin composite material of the present invention is 10% or less. Here, the porosity refers to the ratio of the volume occupied by voids to the bulk volume of the space filling material (in the present invention, the fiber reinforced resin composite material), and is specifically calculated by the following formula.

number

[0020] Generally, the porosity of a fiber reinforced resin composite material can be calculated by a method conforming to JIS K 7075. However, since the fiber reinforced resin composite material according to the present invention uses a natural fiber substrate as the fiber substrate, the porosity cannot be calculated accurately even if the above JIS standard is used as is. In view of this, the present inventors have considered a measurement method and found that the above formula can be applied to calculate the porosity of a fiber reinforced resin composite material including a natural fiber substrate.

[0021] In addition, when the porosity of the fiber reinforced resin composite material increases, the volume of the entire fiber reinforced resin composite material increases relative to a given volume of natural fiber substrate, so that Vf (fiber volume content) decreases. Therefore, it is considered that there is a certain correlation between the porosity of the fiber reinforced resin composite material and Vf (fiber volume content). In addition, the Vf (fiber volume content) of the fiber reinforced resin composite material can usually be calculated by a method conforming to JIS K 7075. However, since the fiber reinforced resin composite material according to the present invention employs a natural fiber substrate as the fiber substrate, Vf (fiber volume content) could not be calculated accurately even if the above JIS standard was used as it is. In view of this, the present inventors have considered a measurement method and found that a predetermined calculation formula can be applied to calculate Vf (fiber volume content) of a fiber reinforced resin composite material having a natural fiber substrate. This calculation formula is shown in the examples.

[0022] As the in-situ polymerization type thermoplastic resin, an in-situ polymerization type phenoxy resin can be suitably used. The reason why the in-situ polymerization type phenoxy resin is preferred as the in-situ polymerization type thermoplastic resin will be explained below. (C) The melting point and curing temperature during heat molding of in-situ polymerization type phenoxy resin are lower than the decomposition temperature of natural fibers (approximately 180°C). Therefore, fiber-reinforced resin composite materials can be molded at temperatures lower than the decomposition temperature of natural fibers. This makes it difficult for deterioration of natural fibers to occur. (D) As mentioned above, the melting point of the in-situ polymerization type phenoxy resin is lower than the decomposition temperature of natural fibers (about 180°C). Therefore, secondary shaping can be performed at a temperature lower than the decomposition temperature of natural fibers. This makes it difficult for deterioration of natural fibers to occur during secondary shaping. (E) In-situ polymerization type phenoxy resin is a mixture of bifunctional epoxy resin and bifunctional phenolic compound in the initial stage (monomer or oligomer state), so it contains many epoxy groups. Generally, natural fibers contain many hydroxyl groups, and it is presumed that the adhesive strength with natural fibers is improved by the interaction between the epoxy groups and the hydroxyl groups. (F) Phenoxy resin has a low water vapor permeability compared to other thermoplastic resins. There is almost no structural difference between phenoxy resins whether they are in-situ polymerized or not, and the effects of molecular weight and branching on water vapor permeability are small. Therefore, by impregnating a natural fiber substrate with in-situ polymerized phenoxy resin, it is possible to produce a fiber-reinforced resin composite material with low moisture absorption (for example, a fiber reinforced resin composite material with a moisture absorption rate of 100 g / m 2 / day) can be expected to be obtained.

[0023] The application fields of the fiber reinforced resin composite material according to the present invention are not particularly limited, but it can be suitably used for electronic device housings such as smartphones, tablet PCs, and notebook PCs, interior materials, flooring materials, fixtures, furniture, etc.

[0024] (Method of manufacturing fiber-reinforced resin composite material) Here, the method for producing a fiber reinforced resin composite material according to the present invention will be described with reference to Fig. 1. Fig. 1 is a flow chart showing the method for producing a fiber reinforced resin composite material according to the present invention.

[0025] First, a precursor composition containing a monomer or oligomer, which is a raw material of the in situ polymerization type thermoplastic resin, and a curing catalyst is impregnated into a natural fiber substrate (impregnation step S101). The molecular weight of the in situ polymerization type thermoplastic resin monomer and oligomer is sufficiently small, and the melt viscosity is low. In addition, the monomer and oligomer have a reactive functional group, and have a high affinity with natural fibers having many surface hydroxyl groups. Therefore, the monomer and oligomer can penetrate into the hollow part of the natural fiber from the wall surface and cross section of the natural fiber, and can be sufficiently impregnated to the substrate center of the natural fiber substrate. Here, the weight average molecular weight of the oligomer is not particularly limited as long as it is a size that can penetrate into the hollow part of the natural fiber and the substrate center of the natural fiber substrate, but is, for example, 300 to 1000.

[0026] The weight average molecular weight (Mw) was determined by GPC measurement. Specifically, a main body HLC8320GPC (manufactured by Tosoh Corporation) equipped with columns (TSKgel SuperH-H, SuperH2000, SuperHM-H, SuperHM-H, all manufactured by Tosoh Corporation) in series was used, and the column temperature was set to 40°C. The eluent was tetrahydrofuran (THF), the flow rate was 1.0 mL / min, and the detector was a differential refractive index detector. The measurement sample was prepared by dissolving 0.1 g of solid content in 10 mL of THF and filtering through a 0.45 μm microfilter, and the injection amount was 50 μL. Mw was calculated by conversion from a calibration curve obtained from standard polystyrene (manufactured by Tosoh Corporation, PStQuick A, PStQuick B, PStQuick C). The data was processed using GPC8020 model II version 6.00 manufactured by Tosoh Corporation.

[0027] The in-situ polymerization type thermoplastic resin monomer and oligomer used in S101 contain a bifunctional epoxy resin and a bifunctional phenol compound as main components, and can be mixed with a reaction catalyst, etc., in a mixer such as a kneader or planetary mixer before impregnation to form a precursor composition. At this time, in order to optimize the mixed state of the raw materials and reaction catalyst, raw materials that have been heated and melted in advance may be mixed, or a solvent such as cyclohexanone or methyl ethyl ketone, xylene resin, reactive diluent, etc., up to about 10% by mass may be added.

[0028] Examples of bifunctional epoxy resins include bisphenol A type epoxy resins (e.g., YD-128, YD-8125 (manufactured by Nippon Steel Chemical & Material Co., Ltd.) and the like), bisphenol F type epoxy resins (e.g., YSLV-80XY, YDF-170, YDF-8170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.) and the like), bisphenol S type epoxy resins, bisphenol acetophenone type epoxy resins, diphenyl sulfide type epoxy resins (e.g., YSLV-120TE Examples of suitable epoxy resins include bisphenol type epoxy resins such as bisphenol fluorene type epoxy resins (e.g., YSLV-80DE (manufactured by Nippon Steel Chemical & Material Co., Ltd.)), diphenyl ether type epoxy resins (e.g., YSLV-80DE (manufactured by Nippon Steel Chemical & Material Co., Ltd.)), and bisphenol fluorene type epoxy resins; biphenol type epoxy resins such as tetramethyl biphenol type epoxy resins (e.g., YX-4000, YX-4000H (both manufactured by Mitsubishi Chemical Corporation)), biscresol fluorene type epoxy resins (e.g., OGSOL CG-500 (manufactured by Osaka Gas Chemical Co., Ltd.)), diphenyl dicyclopentadiene type epoxy resins, alkylene glycol type epoxy resins, dihydroxy naphthalene type epoxy resins (EPICLON4032D (manufactured by DIC Corporation)), dihydroxy benzene type epoxy resins (e.g., ZX-1027, YDC-1312 (both manufactured by Nippon Steel Chemical & Material Co., Ltd.)), and methyl group-substituted derivatives thereof. In order to obtain the above effect (E) (improving the adhesive strength between the in situ polymerization type thermoplastic resin and the natural fiber), the epoxy equivalent of the difunctional epoxy resin is preferably 150-500, and more preferably 150-300.

[0029] Bifunctional phenolic compounds are not limited to those listed below, so long as they are bifunctional. Bisphenol A, bisphenol F (both manufactured by Nippon Steel Chemical & Material Co., Ltd.), bisphenol fluorene, biscresol fluorene (both manufactured by Osaka Gas Chemicals Co., Ltd.), bisphenol E (BisP-E), bisphenol Z (BisP-Z), biscresol fluorene (BisOC-FL), bisphenol AP (BisP-AP), 4,4'-(cyclododecane-1,1-diyl)diphenol (BisP-CDE), 4,4'-(3,3,5-trimethylcyclohexylidene)bisphenol (BisP-HTG), 4,4'-(1,3-dimethylbutylidene)bisphenol (BisP-MIBK), 4,4'-(3-methylcyclohexylidene)bisphenol (BisP-B), 4,4'-(1,3-dimethylbutylide ... isP-3MZ), 4,4'-(1-methylethylidene)bis(2-methylphenol) (S-BOC), 4,4'-methylenebis[2,5dimethylphenyl] (Bis25X-F) (all manufactured by Honshu Chemical Industry Co., Ltd.), bisphenols such as bisphenol S and tetramethylbisphenol S, benzenediols such as hydroquinone, methylhydroquinone, dibutylhydroquinone, resorcin, methylresorcin, catechol, and methylcatechol, naphthalenediols such as naphthalenediol, and biphenols such as biphenol, dimethylbiphenol, and tetramethylbiphenol, among which bisphenol compounds or biphenol compounds are preferred. These dihydric phenol compounds may be used alone or in combination of two or more.

[0030] The curing catalyst used in S101 may be any compound having catalytic ability to promote the reaction between an epoxy group and a phenolic hydroxyl group, among amine-based curing catalysts, phosphorus-based curing catalysts, and imidazole-based curing catalysts, such as tertiary amines, quaternary ammonium salts, cyclic amines, organic phosphorus compounds, and imidazoles. Among them, organic phosphorus compounds such as triphenylphosphine (TPP), tri-o-tolylphosphine (TOTP), and tris(p-methoxyphenyl)phosphine (TPAP), tertiary amines such as 4-dimethylaminopyridine (DMAP), organic phosphorus compounds such as tributyl(methyl)phosphonium dimethylphosphate (PX-4MP), and imidazoles such as 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole (TB-Z) are preferably used. These catalysts may be used alone or in combination of two or more.

[0031] The precursor composition may contain a third component other than the bifunctional epoxy resin, the bifunctional phenolic compound, and the curing catalyst, such as a reaction retarder. When mixing the two liquids, the precursor composition is often heated because of the need to make it uniformly liquefied and reduce the viscosity as much as possible, so it is preferable to contain a reaction retarder to delay the reaction and maintain a low viscosity state. As the reaction retarder, trialkyl borates such as tri-n-butyl borate, tri-n-octyl borate, and tri-n-dodecyl borate, and triaryl borates such as triphenyl borate are used. These are used alone or in combination of two or more.

[0032] The natural fiber substrate is impregnated with the resin composition by various known methods, but from the viewpoint of productivity, a hot melt method (an impregnation method in which a film prepared by applying a precursor composition to a release film is pressed into the film while being heated using a press) is preferably used. By using the hot melt method, S101 (impregnation step) and S102 (prepreg production step) described later can be performed together.

[0033] The natural fiber substrate obtained in S101 is heated, and the precursor composition containing the in-situ polymerized thermoplastic resin monomer or oligomer impregnated in the natural fiber substrate is polymerized to a precursor state to produce a prepreg in which a polymer having a weight average molecular weight of 1,000 to 30,000 is contained in the natural fiber substrate (prepreg production step S102).

[0034] The natural fiber substrate is heated using known methods and equipment. At this time, multiple sheets of the natural fiber substrate may be stacked and vacuum bagged to form an intermediate molding material called a preform.

[0035] The polymer contained in the prepreg obtained in S102 is further heated and polymerized to produce a fiber-reinforced resin composite material according to the present invention, which contains an in-situ polymerization type thermoplastic resin with a weight-average molecular weight of 45,000 or more (composite material production step S103). In S103, shaping of the prepreg into a molded body and polymerization are simultaneously carried out using a hot press machine, autoclave, or the like. The in-situ polymerization type thermoplastic resin produced by polymerization has a large weight-average molecular weight of 45,000 or more and does not easily pass through the walls and cross sections of the natural fibers, remaining in the hollow parts of the natural fibers and in the base material center of the natural fiber substrate, thereby producing a fiber-reinforced resin composite material comprising the in-situ polymerization type thermoplastic resin impregnated in the hollow parts of the natural fibers and in the base material center of the natural fiber substrate.

[0036] In the above-mentioned manufacturing method, S102 (prepreg production step) can be omitted. In this case, the natural fiber substrate obtained in S101 (impregnation step) is heated, and the composition containing the in-situ polymerization type thermoplastic resin monomer or oligomer impregnated into the natural fiber substrate is continuously subjected to polymerization and molding like pultrusion molding to produce a fiber reinforced resin composite material containing an in-situ polymerization type thermoplastic resin with a weight average molecular weight of 45,000 or more (S103). This method also produces a fiber reinforced resin composite material having an in-situ polymerization type thermoplastic resin impregnated into the hollow parts of the natural fibers and the substrate center of the natural fiber substrate.

[0037] The molded article using the fiber-reinforced resin composite material obtained through the above steps may be subjected to post-processing such as drilling, cutting, painting, etc., as necessary. For example, when the in-situ polymerization type thermoplastic resin in the fiber-reinforced resin composite material of the present invention is an in-situ polymerization type thermoplastic phenoxy resin, additional shaping can be performed as a secondary process using a hot press at a temperature (about 180°C) or lower at which thermal degradation of natural fibers begins.

[0038] (Example) In this example, fiber reinforced resin composite materials according to the present invention (Examples) and conventional fiber reinforced resin composite materials (Comparative Examples) were prepared, and the porosity, Vf (fiber volume fraction), mechanical strength, and water absorption of the fiber reinforced resin composite materials were evaluated. In addition, the fiber reinforced resin composite materials in each Example and Comparative Example were also evaluated for discoloration.

[0039] [In-situ polymerization type phenoxy resin composition] Epoxy resin (A1) Bisphenol A type liquid epoxy resin (Nippon Steel Chemical & Material Co., Ltd., YD-128, epoxy equivalent: 174-184g / eq) Phenolic compounds (B1) Bisphenol A (manufactured by Nippon Steel Chemical & Material Co., Ltd.) ·Curing catalyst (C1) Tri-o-tolylphosphine (manufactured by Hokko Chemical Industry Co., Ltd., trade name: TOTP (registered trademark))

[0040] [Examples 1 and 2] In Examples 1 and 2, an in-situ polymerization type phenoxy resin was used as the matrix resin, and a jute cloth material (basis weight: 310 g / m) was used as the natural fiber. 2 (manufactured by Janata) was used. First, 1 part by mass of a cyclohexanone solution containing 188 parts by mass of epoxy resin (A1), 112 parts by mass of phenol compound (B1), and 1 part by mass of curing catalyst (C1) was kneaded with a planetary mixer to obtain a precursor composition. Then, using a reverse roll coater type resin coating device, the precursor composition was uniformly coated on a release paper coated with silicone at a coating temperature of 40°C, and a resin basis weight of 250 g / m was obtained. 2 A precursor composition film having a width of 1 m and a length of 100 m was obtained. Next, the natural fibers were sandwiched between the precursor composition films on both sides and impregnated under heat and pressure at a temperature of 70°C and a linear pressure of 20 kg / cm through a press roll to produce an in-situ polymerization type phenoxy resin natural fiber prepreg (G1). Two sheets of the obtained in-situ polymerization type phenoxy resin natural fiber prepreg (G1) were laminated, and then heat pressed using a heat press under molding conditions of a temperature of 155°C, a pressure of 5 MPa, and a holding time of 2 minutes to produce a flat laminate molding (Example 1) with a thickness of 0.86 mm. Five sheets of the in-situ polymerization type phenoxy resin natural fiber prepreg (G1) were laminated, and then a flat laminate molding (Example 2) with a thickness of 2.05 mm was produced by the same method as described above. Various evaluations were performed on each of the produced laminate moldings.

[0041] [Examples 3 and 4] Natural fiber cotton UD material (weight: 109g / m 2 Except for using a unidirectional reinforced fiber material (manufactured by Toyobo Fibers Co., Ltd.), an in-situ polymerization type phenoxy resin natural fiber prepreg (G2) was produced in the same manner as in Example 1 and Example 2. Note that "UD material" refers to a unidirectional reinforced fiber material. Seven sheets of the obtained in-situ polymerization type phenoxy resin natural fiber prepreg (G2) were laminated so that all layers were in the 0° direction with the fiber direction being 0°, and then heat pressing was performed using a heat press machine under molding conditions of a temperature of 155°C, a pressure of 5 MPa, and a holding time of 2 minutes to produce a flat laminate molding with a thickness of 1.06 mm (Example 3). Eleven sheets of the in-situ polymerization type phenoxy resin natural fiber prepreg (G2) were laminated so that all layers were in the 0° direction with the fiber direction being 0°, and then a flat laminate molding with a thickness of 1.60 mm (Example 4) was produced by the same method as described above. Various evaluations were performed on each of the produced laminate moldings.

[0042] [Comparative Example 1] In Comparative Example 1, a non-in-situ polymerization type phenoxy resin (Fenotetohto YP-50S, weight average molecular weight: 40000, manufactured by Nippon Steel Chemical & Material Co., Ltd.) was used as the matrix resin. First, a resin weight of 250 g / m is applied using a T-die device. 2 A phenoxy resin film 1 m wide and 100 m long was produced. Next, a cloth material made of natural fiber jute hemp (basis weight: 310 g / m2, manufactured by Janata) was prepared as a fiber base material, and the base material was sandwiched between phenoxy resin films on both sides and heated and pressurized through a press roll at a temperature of 160°C and a linear pressure of 20 kg / cm to produce a phenoxy resin natural fiber prepreg (G3). Two sheets of the obtained phenoxy resin natural fiber prepreg (G3) were laminated together, and then heat pressed using a heat press under molding conditions of a temperature of 200°C, a pressure of 5 MPa, and a holding time of 2 minutes to produce a flat laminate molding (Comparative Example 1) with a thickness of 1.24 mm, which was then subjected to various evaluations.

[0043] [Comparative Example 2] In Comparative Example 2, a cotton UD material (basis weight: 109 g / m) was used as a natural fiber. 2 A phenoxy resin natural fiber prepreg (G4) was produced in the same manner as in Comparative Example 1, except that phenoxy resin natural fiber prepreg (G4) was used. Seven sheets of the obtained phenoxy resin natural fiber prepreg (G4) were laminated so that the fiber direction was 0° and all layers were oriented at 0°, and then hot pressed using a hot press machine under molding conditions of a temperature of 200°C, a pressure of 5 MPa, and a holding time of 2 minutes to produce a flat laminate molding with a thickness of 1.00 mm (Comparative Example 2), which was then subjected to various evaluations.

[0044] [Mechanical strength evaluation method] Mechanical strength was evaluated from two perspectives: "tensile strength and tensile modulus" and "flexural strength and flexural modulus." Tensile strength and tensile modulus were evaluated according to JIS K 7164:2005 "Test methods for isotropic and orthotropic fiber-reinforced plastics." Flexural strength and flexural modulus were evaluated according to JIS K7074:1988 "Bending test methods for carbon fiber-reinforced plastics."

[0045] [Water absorption evaluation method] The molded body that had been left for 24 hours under constant temperature and humidity conditions (23°C, 50% RH) was used as a test piece, and after measuring the initial weight (W0), the test piece was immersed in a beaker containing 500 ml of pure water so that the entire test piece was completely below the water surface. After leaving it to stand for 24 hours in a constant temperature and humidity room, the test piece was taken out, the moisture on the surface was wiped off with a Kimwipe, and the weight after immersion (W1) was measured, and the water absorption rate was calculated using the following formula (1). Water absorption rate (%)=(W1-W0) / W0 Formula (1)

[0046] [Evaluation method for Vf (fiber volume fraction)] The density of the compact to be used as the test piece (ρ c ) was measured by the geometric measurement method, and then the matrix resin was dissolved using tetrahydrofuran. The fiber substrate obtained as the residue was dried at room temperature at 23°C for 24 hours, and its weight (W2) was measured, and Vf was calculated using the following formula (2). The literature value was used for the density of natural fibers. Vf(%)=((W2 / W3)×ρ f ) / ρ c Formula (2) W3: Weight of test piece (g) ρf : Fiber density of the test piece (Jute: 1.4g / cm 3 , Cotton: 1.5g / cm 3 )

[0047] [Porosity evaluation method] The porosity of the molded body serving as the test specimen was calculated by the following formula (3).

number

[0048] [Method for evaluating discoloration of fiber-reinforced resin composite materials] The prepregs G1 to G4 were visually evaluated for changes in color before and after they were molded into laminate molded bodies. A rating of ◯ was given when no change was observed other than the color due to the matrix resin, and an X was given when a strong discoloration different from the color of the matrix resin was observed.

[0049] The evaluation results of the examples and comparative examples are shown in Table 1. [Table 1]

[0050] The types of matrix resins are different between Examples 1 and 2 and Comparative Example 1. Referring to Table 1, the porosities in Examples 1 and 2 were 10.0% and 8.0%, respectively, which were smaller than the porosity (35.0%) in Comparative Example 1. In addition, as described above, there is a certain correlation between Vf and porosity, and Vf in Examples 1 and 2 was larger than Vf in Comparative Example 1. Focusing on mechanical strength, the tensile strength, tensile modulus, bending strength, and bending modulus in Examples 1 and 2 were all greater than those in Comparative Example 1. Furthermore, the water absorption in Examples 1 and 2 was smaller than that in Comparative Example 1. The improvement in mechanical strength and the decrease in water absorption in Examples 1 and 2 are believed to be due to the decrease in porosity. Furthermore, in Examples 1 and 2, no discoloration of the fiber reinforced resin composite material during processing was observed, whereas in Comparative Example 1, discoloration of the fiber reinforced resin composite material during processing was observed.

[0051] The types of matrix resins are different between Examples 3 and 4 and Comparative Example 2. Referring to Table 1, the porosities in Examples 3 and 4 were 5.0% and 4.0%, respectively, which were smaller than the porosity (28.0%) in Comparative Example 2. In addition, as described above, there is a certain correlation between Vf and porosity, and Vf in Examples 3 and 4 was larger than Vf in Comparative Example 2. Focusing on mechanical strength, the tensile strength, tensile modulus, bending strength and bending modulus in Examples 3 and 4 were all greater than those in Comparative Example 2. Furthermore, the water absorption in Examples 3 and 4 was smaller than that in Comparative Example 2. The improvement in mechanical strength and the decrease in water absorption in Examples 3 and 4 are believed to be due to the decrease in porosity. Furthermore, in Examples 3 and 4, no discoloration of the fiber reinforced resin composite material during processing was observed, whereas in Comparative Example 2, discoloration of the fiber reinforced resin composite material during processing was observed.

[0052] The present invention is not limited to the above-described embodiments as long as the gist of the present invention is not exceeded. [Explanation of symbols]

[0053] S101 Impregnation process S102 Prepreg production process S103 Composite material production process

Claims

1. A fiber-reinforced resin composite material containing a natural fiber substrate and a matrix resin, The matrix resin is an in-situ polymerized thermoplastic resin, The porosity of the fiber reinforced resin composite material is 20% or less. Fiber reinforced resin composite material.

2. The natural fiber substrate is any one of a unidirectional material, a woven fabric, and a knitted fabric made of a spun yarn of a plant fiber. The fiber-reinforced resin composite material according to claim 1.

3. A method for producing a fiber-reinforced resin composite material according to claim 1 or 2, an impregnation step of impregnating the natural fiber substrate with a precursor composition containing a monomer or oligomer that is a raw material of the in-situ polymerization type thermoplastic resin and a curing catalyst; a composite material production process in which the monomer or oligomer impregnated into the natural fiber substrate by the impregnation process is polymerized to produce a fiber reinforced resin composite material containing the in-situ polymerization type thermoplastic resin having a weight average molecular weight of 45,000 or more; A manufacturing method comprising:

4. A method for producing a fiber-reinforced resin composite material according to claim 1 or 2, an impregnation step of impregnating the natural fiber substrate with a precursor composition containing a monomer or oligomer that is a raw material of the in-situ polymerization type thermoplastic resin and a curing catalyst; a prepreg production step of polymerizing the monomer or oligomer impregnated into the natural fiber substrate in the impregnation step to produce a prepreg in which a polymer having a weight average molecular weight of 1,000 to 30,000 is contained in the natural fiber substrate; A composite material production process in which the polymer contained in the prepreg is further polymerized to produce a fiber reinforced resin composite material containing the in-situ polymerized thermoplastic resin having a weight average molecular weight of 45,000 or more; A manufacturing method comprising:

Citation Information

Patent Citations

  • Fiber-reinforced thermoplastic resin-molded product excellent in heat resistance and method for producing the same

    JP2005068371A

  • Fiber-reinforced thermoplastic resin molded article

    JP2007138361A

  • Spun yarn and intermediate for fiber-reinforced resin, and molded article of fiber-reinforced resin using same

    WO2011062007A1